Prenatal Diagnosis of Atrioventricular Block and QT Interval Prolongation by Fetal Magnetocardiography in a Fetus with Trisomy 18 and SCN5A R1193Q Variant - Horigome, H.; Obata, Mana; Nozaki, Yoshihiro; Kato, Yoshiaki; Takahashi-Igari, Miho; Lin, Lisheng; Hamada, Hiromi (Case Reports in Pediatrics, 2017)
We report a case of fetal trisomy 18 with SCN5A R1193Q variant that presented with sinus bradycardia, 2 : 1 atrioventricular block (AVB), and QT interval prolongation. These complex arrhythmias were diagnosed by fetal magnetocardiography combined with ultrasound findings. Advanced AVB and ventricular arrhythmias were confirmed after birth. Genetic testing of the baby revealed a SCN5A R1193Q variant, which we considered could account for the various arrhythmias in this case.